The missing Europe. Counterfactual narratives and possible worlds - Rutigliano, Stefania (Transnational 20th Century. Literatures, arts and cultures, 2022)
By presenting hypothetical facts with a certain plausibility, counterfactual novels reconsider the great historical events responsible for epochal turning points (Gallagher, Telling It Like It Wasn't) and lead us to reflect on the construction of the current political and cultural order that resulted from them. The Great War recounted by Guido Morselli in Contro-passato prossimo can be read in this sense, along the lines of a convinced and provocative historical anti-determinism that takes on the caricatured face of Giolitti, Lenin and Rathenau and leads to a democratic European community (UNOD) in advance of the EEC; the alteration of the outcome of the Second World War and of the world's political geography in Philip K. Dick's uchronic novel The Man in the High Castle, Telling It Like It Wasn't. Dick's uchronic novel The Man in the High Castle, with Hitler winning the Second World War, a Nazi Germany allied with the Japanese power, and the emphasis on racist and colonial violence of the victorious states; the near uchrony of a Europe unaware of the Holocaust and subject to an enduring Nazi regime in Robert Harris' novel Fatherland. As well as reconsidering topical moments in European political history, the novels indicated restore the flowing lines of converging cultural traditions in an image of the old continent that appears grainy from the assumption of a perspective that is no longer Eurocentric. The counterfactual imagination proves to be an effective tool to deconstruct the stereotyped European cultural heritage: the deviation leading to alternative history questions the age-old paradigm of imitation together with the reality-fiction binomial on which it rests (Kripke, Pavel, Bertoni), redrawing interdisciplinary boundaries (as in the smooth relationship between history and narration proposed by Hayden White in Metahistory). Due to the eminently critical intention of counterfactual literature, fiction exerts friction on reality, recovering its own plausibility: the Europe that does not exist except in the story can be a warning for Europe in the making.